Sickle-trait hemoglobin reduces adhesion to both CD36 and EPCR by Plasmodium falciparum-infected erythrocytes. - Jens E V Petersen; Joseph W Saelens; Elizabeth Freedman; Louise Turner; Thomas Lavstsen; Rick M Fairhurst; Mahamadou Diakité; Steve M Taylor (PLoS Pathogens)
Sickle-trait hemoglobin protects against severe Plasmodium falciparum malaria. Severe malaria is governed in part by the expression of the Plasmodium falciparum Erythrocyte Membrane Protein 1 (PfEMP1) that are encoded by var genes, specifically those variants that bind Endothelial Protein C Receptor (EPCR). In this study, we investigate the effect of sickle-trait on parasite var gene expression and function in vitro and in field-collected parasites. We mapped var gene reads generated from RNA sequencing in parasite cultures in normal and sickle-cell trait blood throughout the asexual lifecycle. We investigated sickle-trait effect on PfEMP1 interactions with host receptors CD36 and EPCR using static adhesion assays and flow cytometry. Var expression in vivo was compared by assembling var domains sequenced from total RNA in parasites infecting Malian children with HbAA and HbAS. Sickle-trait did not alter the abundance or type of var gene transcripts in vitro, nor the abundance of overall transcripts or of var functional domains in vivo. In adhesion assays using recombinant host receptors, sickle-trait reduced adhesion by 73-86% to CD36 and 83% to EPCR. Similarly, sickle-trait reduced the surface expression of EPCR-binding PfEMP1. In conclusion, Sickle-cell trait does not directly affect var gene transcription but does reduce the surface expression and function of PfEMP1. This provides a direct mechanism for protection against severe malaria conferred by sickle-trait hemoglobin. Trial Registration: ClinicalTrials.gov Identifier: NCT02645604.